THE EFFECT OF CLUSTERING TECHNIQUE ON STUDENT’S WRITING SKILL IN RECOUNT TEXT AT THE TENTH GRADE OF SENIOR HIGH SCHOOL - SAFIRA MARPAUNG, REYNALDA (Faculty of Tarbiyah nad Teacher Training, 2022)
The objective of this study is to know the significant effect of Clustering Technique on students’ writing skill in recount text at the tenth grade of Senior High School. This study used quantitative research with quasi-experimental design. It was conducted in tetnth grade of SMA Negeri 1 Rantau Utara. The researcher took 72 students where 36 students for experimental class and 36 students for control class. In collecting the data, the researcher used test in essay test. The researcher used two test, pre-test was given before treatment and post-test was given after treatment in learning process. Then, the researcher analyzed the data by using statistical formulation and Microsoft Excel 2013 with 0,05 significance level. After analyzed the data, the researcher found that the value of tobserved was higher than ttable. It can be seen from tobserved (2,055) > ttable (1,6) at the significance level 0,05 and degree of freedom (df) = 70. It means that the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. It can be conclude that Clustering Technique has significant effect on students’ writing skills in recount text at tenth grade at SMA Negeri 1 Rantau Utara